Effect of organic manures, green leaf manures, liquid organic manures and micronutrients on yield and economics of cotton (Gossypium spp.) - CHANNAGOUDA, R F; BABALAD, H B; DINESHKUMAR, S P (The Indian Journal of Agricultural Sciences, 2015)
A field study was carried out at Main Agricultural Research Station (MARS), Dharwad during kharif 2010-11 and 2011-12 to study the effect of organic manures and micronutrients on cotton. The results of the two years pooled data revealed that, application of enriched compost (EC) (1/3) + vermicompost (VC) (1/3) + gliricidia leaf manure (GLM) (1/3) equivalent to recommended dose of fertilizer (5 tonnes/ha FYM) recorded significantly higher kapas yield (1 944 kg/ha) and mean boll weight (4.57 g) over EC (1/3) + VC (1/3) + GLM (1/3) equivalent to recommended dose of nitrogen. Foliar spray of panchagavya @ 5% recorded significantly higher kapas yield (2 038 kg/ha) and mean boll weight (4.76 g) over foliar spray of bio-digester @ 20% (1 874 kg/ha). Among the organic treatment combinations, combined application of EC (1/3) + VC (1/3) + GLM (1/3) equivalent to RDF with foliar spray of panchagavya @ 5% recorded significantly higher kapas yield (1 999 kg/ha) and mean boll weight (4.70 g) over other organic combinations. Application of EC (1/3) + VC (1/3) + GLM (1/3) equivalent to RDF recorded significantly higher gross returns, net returns and B:C ratio (Rupees 110380, 77335/ha and 3.34, respectively) over other manurial treatments. The foliar spray of panchagavya @ 5% recorded significantly higher gross returns, net returns and B:C ratio (Rupees 108542, 76048 ha and 3.34, respectively) over foliar spray of bio-digester @ 20%. Among the treatment combinations, combined application of EC (1/3) + VC (1/3) + GLM (1/3) equivalent to RDF with foliar spray of panchagavya @ 5% recorded significantly higher gross returns, net returns and B:C ratio (Rupees 113574, 80199/ha and 3.40, respectively) over EC (1/3) + VC (1/3) + GLM (1/3) equivalent to RDN with foliar spray of bio-digester @ 20%. Higher yield, yield parameters and economics can be obtained in cotton with combined application of EC (1/3) + VC (1/3) + GLM (1/3) equivalent to RDF with foliar spray of panchagavya @ 5%.